Optimizing nanoparticle design and surface modification toward clinical translation - Gessner, Isabel (MRS Bull, 2021)
The field of nanomedicine is a rapidly evolving field driven by the need for safer and more efficient therapies as well as ultrasensitive and fast diagnostics. Although the advantages of nanoparticles for diagnostic and therapeutic applications are unambiguous, in vivo requirements, including low toxicity, long blood circulation time, proper clearance, sufficient stability, and reproducible synthesis have, in most cases, bedeviled their clinical translation. Nevertheless, researchers have the opportunity to have a decisive influence on the future of nanomedicine by developing new multifunctional molecules and adapting the material design to the requirements. Ultimately, the goal is to find the right level of functionality without adding unnecessary complexity to the system. This article aims to emphasize the potential and current challenges of nanoparticle-based medical agents and highlights how smart and functional material design considerations can help to overcome many of the current limitations and increase the clinical value of nanoparticles.